Love Thy (Elected) Neighbor? Residential Segregation, Political Representation and Local Public Goods - Oskari Harjunen; Tuukka Saarimaa; Janne Tukiainen (Aboa Centre for Economics (ACE), 2021)
We study the link between geographic political representation and geographic distribution of public goods within local jurisdictions using geo-coded data on politicians, the electorate and elementary school closures. We find that poorer neighborhoods are under-represented. Inequality in geographic representation matters as the probability of school closure halves from about 20% to 10% when a candidate close to the school is randomly elected due to ties in personal vote counts. Highincome residents react to school closures by moving away from their neighborhood. Taken together, residential sorting leads to inequality in representation and public goods across neighborhoods, which further reinforces residential segregation.
Keywords: C21; D72; H75; R23; 330; Geographic representation; random elections; residential segregation; school closure